Assignment of genes for immunoglobulin kappa and heavy chains to chromosomes 6 and 12 in mouse. - Hengartner, H (1978)
Using somatic cell hybrids from fusions of lymphocytes of two different mouse stocks with the myeloma cell line X63-Ag8, we have assigned genes for the immunoglobulin heavy and kappa-type light chains to chromosomes 12 and 6, respectively. The two mouse stocks exhibit karyotypes consisting of nine pairs of metacentric chromosomes as a result of centric fusions of acrocentric chromosomes in different combinations. In the hybrid cells these metacentric chromosomes can be distinguished from the acrocentric chromosomes of myeloma origin, permitting correlation of Ig chain expression with mitotic loss of individual metacentric chromosomes.